f+-7=3

Simple and best practice solution for f+-7=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f+-7=3 equation:


Simplifying
f + -7 = 3

Reorder the terms:
-7 + f = 3

Solving
-7 + f = 3

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + f = 3 + 7

Combine like terms: -7 + 7 = 0
0 + f = 3 + 7
f = 3 + 7

Combine like terms: 3 + 7 = 10
f = 10

Simplifying
f = 10

See similar equations:

| -10+m=-24 | | x+-9=6 | | 3+b=-21 | | f+-13=-19 | | 45=x/3 | | z=y/10 | | -21-y=-3 | | j-(-13)=9 | | -17-s=-21 | | -17-s=21 | | 7/2y=56 | | -5(n-3)+2(n+1)= | | 3-d=23 | | -21-g=-31 | | f(x)=4x^2+7x-3 | | 196x^2+98x+2=0 | | x^4-4x+2= | | 5y=ax+1 | | 3(w-3)=6w+1-3(-5-2) | | x^2(xsquared)-15=154 | | 4ln=x | | .5x(3x)=65 | | 7*(3b+4/x)=43 | | T/4-71= | | 1-7T/4 | | 6(-3x-2)+9=-7(x+5)-1 | | 6x+6=-2x+37 | | p/p^5= | | p/p^-5 | | k=mx | | (7x)9+6= | | 2cos(6x-15°)=10/7 |

Equations solver categories